Extrato da pele do amendoim e tocoferol como aditivos naturais para prevenção da oxidação lipídica de maionese - Tonini, Paulo Rangel Santos (2023)
Lipid oxidation has gained great prominence in food industry research and the use of antioxidants of natural origin such as tocopherol and peanut skin extract stand out for having phenolic compounds and may have antioxidant potential. In this context, the objective of the present work was to evaluate the technological properties of mayonnaise produced with soybean oil and pumpkin seed oil, added tocopherol and peanut skin extract (PSE) as natural antioxidants, during storage at room temperature. The extract was obtained using a customized unit, where the peanut skin (cultivar Runner) underwent extraction with pressurized liquid in ethanol and water (70:30 v/v) at 10 MPa, 80 °C, flow rate 3 mL/min, for 40 minutes and rotary-evaporated. As a starting point, a PSE solubility test was carried out in the combination of soybean and pumpkin oil in the proportion 80/20 w/w, with vortexing for 5 minutes and subsequent visual analysis. The phenolic compounds in PSE were quantified by High Performance Liquid Chromatography (HPLC). From this, a central rotational composite design was carried out with the variables peanut skin extract (PSE) and tocopherol to evaluate the color, pH, texture and FTIR-ATR responses. The color, texture and FTIR-ATR data were also discussed using common dimension analysis (COMDIM) to observe patterns and groupings. It was possible to observe that for all parameters, the effects of the variables observed in the ANOVA for the amounts of natural antioxidants used were not significant, and it was not possible to establish a predictive model. The ΔE values indicate that there was a color change for all samples over the days, regardless of the number of variables. The pH increased over the days and the texture parameters decreased during storage (p<0.05). For oxidation, the samples expressed peaks typical of edible oils, however it was not possible to observe oxidation through FTIR-ATR. The COMDIM data confirmed what was observed in the t-student test and model adjustment analysis by ANOVA, since, for color and texture, the observed separation is related to storage time and for FTIR, a grouping pattern was not observed. Therefore, it is concluded that mayonnaise had similar behavior and this difference is linked to the time factor due to oxidation and not necessarily to the amount of antioxidant, which had a non-significant effect for the quantities analyzed. In oxidation, the method was effective for determining organic compounds, however it was not possible to observe lipid oxidation. However, since there was the presence of phenolic compounds determined by HPLC in the extract and that the variables were not responsible for altering the characteristics of the product, it is possible that greater quantities of them and other tests such as rancimat, can be analyzed in studies focusing on in natural antioxidants.